PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT UNILEVER INDONESIA, TBK - Pujiati, Puput; Susmonowati, Trinik (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to determine the impact of promotion costs and distribution costs on sales volume at PT Unilever Indonesia. Tbk. The research method used is the quantitative descriptive method. The data collection technique used is secondary data, including analysis of the financial statements of PT Unilever Indonesia. The sampling technique used in this study is a purposive sampling; covering data on promotional costs and distribution costs incurred by PT Unilever Indonesia, Tbk, and sales volume over a span of 10 years (.2013 to 2022). The data analysis used is multiple linear regression analysis using IBM Statistics software version 26. The results of this study indicate that Promotion Costs have an impact on Sales Volume by 72.6%. Distribution Costs have an impact on Sales Volume by 91.7%. Promotion Costs and Distribution Costs have a significant impact on Sales Volume. Promotion Costs and Distribution Costs affect the Sales Volume variable simultaneously with a score of 0, 948 or 94.8%, where 5.2% is affected by other variables that are not included in this research.